2008
DOI: 10.1021/ja803494v
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Interactions of Cu(II) with α and β-Synuclein: Bridging the Molecular Gap between Metal Binding and Aggregation

Abstract: The aggregation of alpha-synuclein (AS) is a critical step in the etiology of Parkinson's disease (PD) and other neurodegenerative synucleinopathies. Protein-metal interactions play a critical role in AS aggregation and might represent the link between the pathological processes of protein aggregation and oxidative damage. Our previous studies established a hierarchy in AS-metal ion interactions, where Cu(II) binds specifically to the protein and triggers its aggregation under conditions that might be relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
216
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(238 citation statements)
references
References 75 publications
20
216
0
2
Order By: Relevance
“…A similar result was also obtained in an F4W/H50S mutant, suggesting that the high-affinity N-terminal Cu(II)-binding site revealed by W4 fluorescence quenching is not perturbed by H50 that is not likely to be involved (Lee et al 2008). Two independent non-interacting copperbinding sites were also detected in the N-terminal region in another study based on a thorough spectroscopic characterization of the a-synuclein-Cu(II) complexes (Binolfi et al 2008). Using a mass spectrometry-based approach, the investigators unequivocally demonstrated the direct role of Met1 as the primary anchoring residue for Cu(II).…”
Section: Copper and A-synucleinsupporting
confidence: 72%
See 1 more Smart Citation
“…A similar result was also obtained in an F4W/H50S mutant, suggesting that the high-affinity N-terminal Cu(II)-binding site revealed by W4 fluorescence quenching is not perturbed by H50 that is not likely to be involved (Lee et al 2008). Two independent non-interacting copperbinding sites were also detected in the N-terminal region in another study based on a thorough spectroscopic characterization of the a-synuclein-Cu(II) complexes (Binolfi et al 2008). Using a mass spectrometry-based approach, the investigators unequivocally demonstrated the direct role of Met1 as the primary anchoring residue for Cu(II).…”
Section: Copper and A-synucleinsupporting
confidence: 72%
“…Then, they reached the conclusion that the high-affinity Cu(II)-binding site in a-synuclein (K d \ 1 lM) is the one in which the N-terminal amino nitrogen of Met1 acts as the anchoring group together with Asp2 and maybe a water molecule. They also defined a second, lower-affinity binding motif for Cu(II) (K d * 50 lM) centered around His50 as evaluated in a CD titration of the a-synucleinCu(II) complex in which the Cu(II)-His50 contributions to the spectra were singled out (Binolfi et al 2008). A further contribution to this subject was provided by potentiometric and spectroscopic studies carried out on truncated N-terminal and H50 region models of a-synuclein fragments.…”
Section: Copper and A-synucleinmentioning
confidence: 99%
“…Nevertheless, numerous studies proposed only a single high affinity coordination mode, with disagreement regarding the role of Met1 and His50 and/or overlooking the effect of pH-dependent equilibrium. [20][21][22][27][28][29][30][31][32][33][34][35][36] To characterize the Cu II -binding properties, 65 CuCl 2 was first titrated into a solution of aSyn56 at pH 7.4 and analyzed using X-band EPR spectroscopy. Between 0-1 equiv Cu II , two sets of hyperfine features could be distinguished (Figure 1 a), indicating the presence of more than one coordination mode.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned earlier, a-Syn binds to copper and iron (46,48,49), and a-Syn aggregation is stimulated in the presence of these metals (37,50). This has led us to examine whether the toxicity of extracellular synuclein proteins was exacerbated in the presence of metals.…”
Section: Copper and Oligomer Toxicitymentioning
confidence: 97%